EMBEDDED WEBSERVER FOR METEOROLOGICAL DATA MONITORING - Ashish Shukla, Abhay Shukla, Rituraj Kushwaha, Shail Dubey, Pooja Diwivedi (Elementary Education Online, 2020)
Meteorological data monitoring in India currently involves manual methods or data feeding into personal computers, followed by transfer to the internet. This approach results in non-real-time data and poses challenges in resource management for both governmental and private sectors, such as industries. The proposed solution suggests replacing personal computers and large servers, which consume significant power, with a small, energy-efficient Embedded Web Server. This upgrade would provide real-time data, facilitating more effective resource management and planning for government and private entities alike. The Embedded Web Server utilizes an ARM processor and can connect directly to LAN or the internet. Meteorological data plays a crucial role in diverse applications such as agriculture, industries, and predicting natural disasters like floods.